2021
DOI: 10.22490/21456453.4641
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos de la fisiología y el cultivo del lulo (Solanum quitoense LAM.) en Colombia: una revisión

Abstract: Contextualización: el lulo es un fruto promisorio de alta demanda en los mercados, debido a sus excelentes propiedades organolépticas, además de ser fuente importante de vitaminas y minerales.    Vacío de conocimiento: en los últimos diez años se han desarrollado múltiples investigaciones sobre la ecofisiología de la planta de lulo, sin que exista una  revisión de literatura de este.    Propósito del estudio: recopilar aspectos generales del cultivo, incluyendo los principales requerimientos agronómicos y aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…It should be noted that this conversion of acids into sugars is essential for quality (flavor and aroma) and nutritional value in fruits (VALLARINO; OSORIO, 2019). The TA presented significant differences between 1-MCP doses at 4 °C (2.57) and 16 °C (2.24), as reported by Álvarez-Herrera et al (2022), who stated that 1-MCP influences the metabolism of carbohydrates and organic acids. This confirmed that, when feijoa fruits are refrigerated, organic acids degrade at a lower rate than when fruits are stored in the environment.…”
Section: Titratable Acidity (Ta)supporting
confidence: 66%
“…It should be noted that this conversion of acids into sugars is essential for quality (flavor and aroma) and nutritional value in fruits (VALLARINO; OSORIO, 2019). The TA presented significant differences between 1-MCP doses at 4 °C (2.57) and 16 °C (2.24), as reported by Álvarez-Herrera et al (2022), who stated that 1-MCP influences the metabolism of carbohydrates and organic acids. This confirmed that, when feijoa fruits are refrigerated, organic acids degrade at a lower rate than when fruits are stored in the environment.…”
Section: Titratable Acidity (Ta)supporting
confidence: 66%
“…Indeed, the highest N concentration was obtained in roots of plants under T1 containing the lowest compost content (40%), which may be attributed to a possible better balance between NO 3 − and NH 4 + in the substrate mixture for these tissues (Table 1). This species positively responds to increasing N applications, applied to both the soil and the leaves [6]. Conversely, all other macronutrients in roots were higher in plants under T3, which contained 80% compost.…”
Section: Macronutrient Concentrations In Plant Tissuesmentioning
confidence: 92%
“…Moreover, research on its cultivation is still in its infancy [5]. In fact, the lulo-growing industry has developed as a result of initiatives taken by the growers themselves, without significant scientific support in terms of research, technology and innovation [6]. Therefore, there is a big need for carrying out research aimed at overcoming some technical limitations that currently limit its expansion and competitiveness, including Horticulturae 2022, 8, 1200 2 of 13 studies on the effect of substrates on germination and production of healthy seedlings in containers under greenhouse or nursery conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Ref. [72] found that, by removing Mg from the nutrient solution, the height of the lulo plants decreased significantly and possibly lacked Mn, Mo y Cu.…”
Section: Foliar Analysismentioning
confidence: 96%